Impact of social media platforms on the construction of social networks among the middle class - Li, Ziming; Samsurijan, Mohamad Shaharudin (Edelweiss Applied Science and Technology, 2025)
This study systematically explores the impact mechanism of social media platforms on the construction of social networks among the middle class, focusing on how platforms reshape the path of social capital accumulation, strengthen class identity boundaries, and regulate cross-group interaction patterns. Based on the framework of social capital theory and mediatization theory, the study proposes a "platform-mediated class segmentation" model, revealing that social media dynamically reconstructs the structure of social networks through the synergy of algorithmic logic and user behavior. Using a mixed research and structural equation model (SEM) approach, a questionnaire survey was conducted on 500 middle-class users in first-tier cities (to analyze the size of social networks, interaction frequency, and intensity of algorithm usage quantitatively), and in-depth interviews were conducted with typical users (to analyze content strategy and platform perception qualitatively). The study found that social media significantly expanded weak relationship networks (β=0.32, p<0.01). Still, the homogenized content pushed by algorithms led to a 17% decrease in cross-class interactions (p<0.01), forming a closed circle. Users displayed their identities through visual symbols ("Ins-style" pictures accounted for 68%) and textual practices ("middle-class standard" discourse frequency 4.2 times/1,000 words), and 41% of the respondents adopted "selective visibility" behavior (blocking low-income groups) to maintain their class image. The study also reveals the contradictory dependence of users on the platform. The conclusion shows that social media reshapes the middle-class social network through algorithm-driven visibility distribution and cultural symbol encoding mechanisms, providing channels for resource flow and exacerbating class closure. On the theoretical level, this study integrates mediatization theory and class analysis and proposes the concept of "platform-mediated social capital." In practice, it is recommended to optimize algorithm design to promote cross-class interaction, and policies need to focus on the potential inhibition of class mobility by platform mechanisms. The limitation of the study is that the samples are concentrated in the urban middle class. In the future, it is necessary to include urban-rural comparisons and diachronic tracking to improve the dynamic model of class differentiation.